2017
DOI: 10.1093/fampra/cmw126
|View full text |Cite
|
Sign up to set email alerts
|

Patient experience of primary care and advance care planning: a multicentre cross-sectional study in Japan

Abstract: We found that better patient experience of primary care was strongly associated with ACP discussion. Our findings reinforce the significance of patient experience in primary care as part of quality end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 21 publications
4
38
0
2
Order By: Relevance
“…According to previous studies, patient experience affects various behaviors, such as adherence to treatment, cancer prevention activities, emergency department visits, and advance care planning. [27][28][29][30] The results of this study have contributed additional findings on the association between patient experience and healthcare utilization. This is the first confirmatory longitudinal study to reveal the association between patient experience of primary care and bypassing a primary care gatekeeper to seek care at a higher- PCAT is an internationally established measure for the evaluation of patient experience of primary care.…”
Section: Discussionmentioning
confidence: 88%
“…According to previous studies, patient experience affects various behaviors, such as adherence to treatment, cancer prevention activities, emergency department visits, and advance care planning. [27][28][29][30] The results of this study have contributed additional findings on the association between patient experience and healthcare utilization. This is the first confirmatory longitudinal study to reveal the association between patient experience of primary care and bypassing a primary care gatekeeper to seek care at a higher- PCAT is an internationally established measure for the evaluation of patient experience of primary care.…”
Section: Discussionmentioning
confidence: 88%
“…The total score reflects an overall measure of the quality of core primary care principles. Previous studies have shown that the JP-CAT has good reliability and validity, 20 and that it is associated with the adoption of breast cancer screening, 22 advanced care planning discussions, 23 and the bypassing of PCPs. 24…”
Section: Patient Experience Of Primary Carementioning
confidence: 99%
“…In the opinion of patients, families, and health care professionals, the family physician (FP) is the key professional for the discussion of ACP [4,[6][7][8][9]. Previous studies investigated the attitude of FPs toward ACP and the facilitators of or barriers to discussing ACP with FPs [10]; limited information is currently available on frequency of and topics involved in the ACP discussion among patients, their family members, and FPs [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%